The urgency of a gender-based approach to counter terrorism in Indonesia: a look into the European policies - Putri, Devita Kartika (Legality : Jurnal Ilmiah Hukum, 2022)
In recent years, Indonesia has faced a rising rate of women's participation in terrorism. The Presidential Decree No. 7 of 2021concerning the National Action Plan for the Prevention and Countering of Violent Extremism that Leads to Terrorism 2020-2024 mentioned ‘gender mainstreaming’ to counter terrorism without elaborating how this gender-based approach was to be conceptualized in executing policy and regulatory framework. Therefore, this study analyzes the policies of European states. The objective of this study is to learn from the practice of European states to see how a gender-based approach could be further conceptualized under Indonesia’s counter-terrorism policy and regulatory framework. This article was based on normative research, employing both primary and secondary data. Furthermore, the discussion was based on three approaches: statutory, comparative, and conceptual approaches. The result of the study shows that a gender-based approach requires the Indonesian policy and regulatory framework to treat counter-terrorism as a cross-cutting issue between gender and the fulfillment of human rights.